Automated System for Computationof Burnt Forest Region using Image Processing - Ghosh, Bibek Ranjan; Banerjee, Siddhartha; Saha, Attyuttam (International Journal of Computer Sciences and Engineering, 2025)
Fire is one of the major problems that are causing great loss to property and ecosystem in today’s world. Fires not only affect the characteristics of forests but it also affects human lives and livelihood. Due to the lack of specific techniques for calculation of burnt regions of forests, researchers use different methods. In this research, an automated approach is developed to determine the significant burnt area of forest using different image processing techniques. The proposed method is compared with other existing methods and is found to be capable in more precise measurement of the burnt area.